2013
DOI: 10.1111/bjd.12134
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin barrier function in podoconiosis: measurement of stratum corneum hydration and transepidermal water loss

Abstract: Patients with podoconiosis have significantly lower SC hydration in the skin of their lower legs and feet than controls, which may lead to cracking and splitting, and increased risk of lymphoedema and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…Williams et al [22] noted that expandable clay minerals, particularly illite-smectite, had the most pronounced antibacterial properties due to extreme pH and Fe concentration, and Otto and Haydel [21] demonstrated that illite-smectite rich clay mixtures acquire powerful antibacterial activity due to their positive correlation with concentration of Cu 2+ and Zn 2+ ions, rather than their negative correlation with Fe 3+ or lack of correlation with pH. These effects of clay mineral types in infection and our finding of strong associations between podoconiosis and soil smectite concentrations may help explain the pathogenesis of episodes of super-infection and acute adenolymphangitis (a frequent complication of podoconiosis characterized by hot, painful, and reddened swelling of the lymphedematous legs) [23-25]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Williams et al [22] noted that expandable clay minerals, particularly illite-smectite, had the most pronounced antibacterial properties due to extreme pH and Fe concentration, and Otto and Haydel [21] demonstrated that illite-smectite rich clay mixtures acquire powerful antibacterial activity due to their positive correlation with concentration of Cu 2+ and Zn 2+ ions, rather than their negative correlation with Fe 3+ or lack of correlation with pH. These effects of clay mineral types in infection and our finding of strong associations between podoconiosis and soil smectite concentrations may help explain the pathogenesis of episodes of super-infection and acute adenolymphangitis (a frequent complication of podoconiosis characterized by hot, painful, and reddened swelling of the lymphedematous legs) [23-25]. …”
Section: Discussionmentioning
confidence: 98%
“…Our univariate analysis finding of elevated zirconium in podoconiosis-endemic areas may suggest that this element plays another role, such as in facilitating dryness and cracking of skin on the feet. A recent study in Ethiopia showed that podoconiosis cases had lower stratum corneum hydration than unaffected controls, resulting in skin dryness and cracking which, in turn, may facilitate the ingress of mineral particles or microorganisms through the skin barrier [23]. The ability of zirconium to accumulate in skin stratum corneum and sometimes to cause skin granuloma (inflammation) has been documented [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 4 Sequence of skincare-related intervention used on different anatomical sites of the lower legs of older people study was found which measured SCH and TEWL in those with podoconiosis, and it used these probes (Ferguson et al, 2013). The study indicates the positive effects on SBF of soaking for 30 min a day for 5 days in the treatment combination containing 2% glycerine due to improvements in SCH, although not TEWL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the stratum corneum in podoconiosis patients is often compromised and visibly damaged and it is likely that cracked, compromised skin allows sufficiently small soil particles to enter into the dermal layer ([18]). Furthermore, it has been shown that people with podoconiosis have significantly lower levels of hydration in their outer layer of skin (stratum corneum), which is likely to lead to cracking and splitting ([19]). Prolonged and repeated exposure to the abrasive components of the volcanic soil (e.g., quartz) could exacerbate stratum corneum degradation and enable nano- and submicron particles to penetrate the viable epidermis.…”
Section: Introductionmentioning
confidence: 99%